Development of Android-Based Linear Program Teaching Materials with an Ethnomatematics Approach to Improve Students’ Mathematical Problem Solving Ability - Novitasari, Fitri; Walid, Walid (Department of Mathematics, Universitas Negeri Semarang, 2022)
This study aims to determine process of developing teaching materials for android-based linear programming with an ethnomathematics approach that was valid, practical, and effective to improve students' mathematical problem solving abilities. This study uses research and development (R&D) methods with modifications to the ADDIE model developed by Dick and Carry Analysis, Design, Development or Production, Implementation and Evaluation. Data collection using test techniques and non-test techniques. The data analysis technique used a Likert scale, Guttman scale, one-sided average s test, proportion test, and N-Gain test.The results showed that the teaching materials had very valid criteria with an average percentage of material validity test of 93.84% and media validity test of 86.67%, very practical with an average practicality test of 90%, and effective for improving mathematical problem solving skills. students which include: (1) mathematical problem solving abilities of students who are taught using teaching materials meet individual mastery; (2) the proportion of completeness of students' mathematical problem solving ability test results after using teaching materials is more than 80% so as to achieve classical mastery. (3) based on the results of the pretest and posttest showed that the teaching materials were able to improve students' mathematical problem solving abilities where the average posttest score was greater than the average pretest score with an N-Gain result of 0.5659 on medium criteria. So, it can be concluded if the teaching materials are valid, practical, and effective so that they are feasible to be used in learning mathematics to improve students' problem solving abilities.